An Examination of the Impact of Blue Heat Treatment on the Forced Caused by the Vertical Motion of Endodontic Files - Tanveer Ahmed Siddiqui, Aisha Shujat, Shabir Ahmed Jagirani, Zaheer Hussain Chachar, Fozia Rajput, Madiha Khalid Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the vertical forces produced during canal shaping by the Reciproc Blue (RB) and Reciproc (R) systems. Place and Duration: In the Operative Dentistry Department, Altamash Institute of Dental Medicine Karachi for one-year duration from January 2022 to December 2022. Methods: A total of 32 maxillary premolar teeth were selected, each with two distinct constricted and straight canals. Every tooth was positioned in a standing position on a platform attached to a force analysing device after access cavity preparation (M5-20 Advanced Digital Force Gauge; Mark-10 Corporation, NY, USA). Until the K file size was up to 15, the glide route was prepared manually. Then, using an R25/RB25 file, all of the groups’ canals were completely shaped (0.08 taper, size 25). The canal was shaped with a mild and steady pressure on the file that produced a gradual, 2 mm amplitude "in-and-out" movement. It took three attempts for the file to successfully reach the WL. The canal was irrigated and recapitulated with sodium hypochlorite (1%) solution following each insertion. The Student’s t-test was used to analyze the shaping time. The Mann Whitney test was applied to analyse the upward and inward peak forces. With a 95% level of confidence, SPSS software was used for all statistical analyses. Results: A single file was inserted into each root canal successfully three times for shaping till the WL achieved. With each additional file insertion, the overall real-time force increased in each group grew. The R group displayed lower peak forces in comparison to the RB group in the 3 insertions, and both groups inward peak forces varied from 1.76 to 8.64 N. (P<0.05). Complete canal shaping of the RB and R systems took an average of 24.30±3.98 s and 21.91±3.56s, respectively (P>0.05). During canal shaping in this experiment, no file fracture occurred. Conclusion: The forces generated during canal shaping were influenced by the blue heat treatment. Higher inward peak forces were higher in the RB file than the R file. Keywords: Root canal preparation, Endodontics, vertical force and shaping time.